Effect of pH Variations in Water Immersion on Concrete Compressive and Tensile Strength - Sunujaya, Muhammad Alim; Soehardjono, Agoes; Nuralinah, Devi (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2025)
Chemical elements, especially acids, can gradually cause concrete to deteriorate. When concrete deteriorates, the bond between the cement paste and aggregates weakens, decreasing compressive strength. This study aims to analyze the influence of pH levels on concrete's compressive and tensile strength. Concrete specimens with characteristic compressive strengths of 20, 25, and 30 MPa were immersed in solutions with pH levels of 4 (acidic), 7 (neutral), and 10 (alkaline) for 28 days. These study results are from experiments conducted at Brawijaya University, Malang. The results showed that an acidic environment can decrease the compressive strength of concrete. In contrast, immersion in an acidic solution (pH 4) significantly reduces the tensile strength compared to immersion in neutral and alkaline solutions. Concrete with higher characteristic compressive strength tends to have higher tensile strength, even when exposed to acidic environments. The conclusion drawn from this study is that an acidic environment (pH 4) significantly negatively impacts the tensile strength of concrete. Concrete with higher characteristic compressive strength exhibits better resistance to acidic environments. Neutral (pH 7) and alkaline (pH 10) environments yield better results than acidic environments.